PERFORMA PROPORSI ZERO-INFLATION PADA REGRESI ZERO-INFLATED NEGATIVE BINOMIAL - AMALIANA, LUTHFATUL; SA’ADAH, UMU; WARDHANI, NI WAYAN SURYA (E-Jurnal Matematika; Vol 8 No 2 (2019)DO - 10.24843/MTK.2019.v08.i02.p238, 2019)
Tetanus Neonatorum (TN) is an infectious disease that could be prevented by immunization. East Java Province is the highest numbers of TN case in Indonesia. TN data in East Java contain overdispersion and big proportion of zero-inflation (71,05%). The data containing overdispersion and zero-inflation are more appropriately analyzed by using Zero-Inflated Negative Binomial (ZINB) regression. The aim of this study are: (1) to know the perform of proportion of zero-inflation for ZINB model and (2) to obtain the optimal proportion of zero-inflation for TN data. The result of this study indicates that the optimal proportion of ZINB model is 64,52%.